Influence of magnetic field-induced anisotropic gluon pressure during pre-equilibrium in heavy-ion collisions: A faster road toward isotropization - Ayala, Alejandro; Mizher, Ana Julia [UNESP] (American Physical Society (APS), 2024)
Magnetic fields of a large intensity can be generated in peripheral high-energy heavy-ion collisions. Although their intensity drops fast and, moreover, it is not clear whether these fields last long enough to induce a magnetization during the quark-gluon plasma phase, most of the models and simulations predict a significant intensity that lasts up to proper times of order 1 fm after the beginning of the reaction, which is a typical time for the hydrodynamical phase to start. This interval of time is referred to as the pre-equilibrium stage. The evolution of the reaction during pre-equilibrium is thus likely to be influenced by these fields. In this work we adopt a strong field approximation to study the effects of the magnetic field-induced anisotropy on the gluon pressure. We include this anisotropy within the description obtained by means of effective kinetic theory and explore the consequences to reach isotropization at proper times of order 1 fm. We show that when including the magnetic field effects, isotropization is achieved faster.